(untitled) (Superficies y Vacío, 2013)
In this work we present the analysis of the inhomogeneous broadening of Photoreflectance (PR) and Photoluminiscence (PL) spectra in InGaAs/InAlAs quantum wells. The sample was grown by means of Metal Organic Chemical Vapor Deposition (MOCVD) with well widths in the range from 6.5 to 10.5 nm. PR measurements were performed in the temperature range between 220 and 300 K while the PL measurements were made in the temperature range from 11 to 300 K. Comparative analysis of line shapes of the PR and PL experimental spectra reveals an inhomogeneous broadening in both measurements, which is attributed to local stresses in the well-barrier interface. From the analysis of the PR and PL spectra, we obtained the temperature dependence of the broadening parameters, allowing the identification of effects of exciton-phonon interaction in optical transitions studied by both optical techniques.